GREEN PROTOCOLS FOR AMIDATION REACTIONS (International Journal of Food and Nutritional Sciences, 2022)
Amide functionality is gaining importance day by day because of wide use in synthetic organic chemistry as well as biological, medicinal and pharmaceutical field. Classical amidations are carried out using homogenous metal catalyst but several drawbacks have come infront. New generation research demands more advanced catalytic approach for amidation where green chemistry takes its entry. This paper provides an overview of metal free and photocatalytic amidation of aldehydes and alcohols. It also covers enzyme catalyzed amidation reactions of both established and newer methods and compares the efficiency along with which will be very helpful for new generation researchers with a sensible and educated choice of catalyst. Remaining challenges in this process are also carefully analyzed.